PEMBANGUNAN HUKUM BERDASARKAN KEADILAN SOSIAL BAGI SELURUH RAKYAT INDONESIA - Darma Pratiwi, Agustina Ni Made Ayu; Lestari, Anak Agung Adi (JURNAL PANAH KEADILAN, 2025)
Pancasila is the ideology that upholds the law and guides the political process. Therefore we must necessitate law and politics based on Pancasila, namely Divinity, Humanity, Unity, Democracy and justice. One of the Pancasila values ​​that the writer will discuss is justice, because the word justice has a broad scope. What kind of justice is needed by the Indonesian people. Therefore, the formulation of the problem from this research is how is the development of law based on social justice for all Indonesian people. This research uses normative legal research methods. Pancasila provides a guarantee of justice that fulfills the concept of justice contained therein, Pancasila provides the best protection for all citizens, regardless of citizen status, Pancasila provides protection without exception Pancasila is the basis or ideology of the Indonesian nation or national ideology.